Analysis of the Bearing Characteristics of Single Piles under Vertical and Torsional Combined Loads - Shun-Wei Wang; Jie Jiang; Chen-Zhi Fu; Xiao-Duo Ou; Juan Tang (Advances in Civil Engineering)
To investigate the bearing characteristics of single piles under the combined action of vertical loads (V) and torque (T) on a pile head, the displacement governing equations of the pile shaft were proposed in consideration of the load transfer method, and the nonlinear solution of a single-loaded pile (vertical load or torque) was calculated by the finite difference method. According to the above mentioned investigation, a new numerical analysis model was proposed to modify the vertical and circumferential ultimate friction resistance of the pile side. Subsequently, the nonlinear solutions of single piles under the combined loads of V-T loading with different loading paths were obtained by MATLAB programming, and the bearing capacity envelopes were plotted. Based on the comparison with the existing research results, the correctness of the theoretical calculation method proposed in this article was verified. The results show that compared with a single loaded pile (V or T), with the action of the V-T combined loads, the bearing capacity of a single pile will decrease, and the single piles under the V⟶T loading path will have a higher bearing capacity than those under the T⟶V loading path. When the aspect ratio is comparatively small, the influence of the loading path is negligible; however, when the aspect ratio is comparatively large, it is necessary to avoid the preliminary application of the torque to a single pile to prevent the decrease in the ultimate bearing capacity on account of the formation of the T⟶V loading mode. The deformation of the pile body mainly occurs in the range from 0 to 0.6L, so effective deformation reduction can be achieved by reinforcing the shallow foundation. It is inadvisable for a single friction pile to be used to improve the bearing capacity by increasing the concrete grade.